Provisioning QOS using diffserv with hierarchical scheduling - Abidin, H. Z.; Din, N. M.; Fisal, N. (2004)
Internet was designed mainly for data communication applications such as file transfer and electronic mail that does not guarantee any specific quality-of-service (QoS). QoS such as end-to-end delay might be important for other types of multimedia communications that involve real-time traffic such as voice and video. Differentiated Services (DiffServ) is one of the mechanisms that could provide QoS. In DiffServ, traffics are treated differently based on their QoS requirements. This paper suggests the use of hierarchical scheduling technique in DiffServ in order to provide QoS in IP network. Network performance is observed based on our simulation work using Network Simulator (ns2).